RNA signaling in skeletal muscle: the central role of microRNAs and exosomal microRNAs - Liu, Shunshun; Dong, Huan (Frontiers in Cell and Developmental Biology, 2025)
Skeletal muscle development and adaptation are governed by complex regulatory networks that coordinate gene expression, signaling pathways, and intercellular communication. Among the emerging key regulators are microRNAs (miRNAs) and exosomal microRNAs, which function as critical modulators of skeletal muscle growth, differentiation, regeneration, and metabolic adaptation. The review explores the acknowledged contributions of miRNAs, both intracellular and those encapsulated within exosomes, to the regulation of skeletal muscle physiology. We highlight their involvement in major molecular pathways, including PI3K/Akt/mTOR, TGF-β/Smad, Wnt/β-catenin, and AMPK signaling, and their impact on processes such as myogenesis, hypertrophy, atrophy, and mitochondrial function. Emphasis is placed on the critical role of exosomal miRNAs in orchestrating signaling pathways that enable communication among cells in the muscle milieu and with peripheral tissues. Ultimately, the review addresses the clinical relevance of miRNAs, including those derived from exosomes, emphasizing their prospective roles as diagnostic tools and intervention points in muscle-related conditions. In sum, the review elucidates the broad landscape of RNA-related regulatory processes in skeletal muscle and projects forward-looking strategies for translational exploration in this rapidly developing scientific domain.